Development of an assessment instrument to measure high school students' 21st century skills in social interaction - Magfirah Isnayah; Daroe Iswatiningsih; Siti Inganah; Rafiah Mahmudah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to develop an assessment instrument to measure 21st-century skills—critical thinking, creativity, collaboration, and communication (4C)—in the context of social interaction learning for tenth-grade high school students. This research is grounded in the practical challenges faced by teachers, particularly the difficulty of assessing 4C competencies systematically due to the absence of standardized and context-specific assessment instruments in Sociology learning. In many schools, assessment practices still focus on cognitive outcomes, leaving social and interaction-based competencies underassessed. The study employed a Research and Development (R&D) approach using the Lee and Owens model, which includes five stages: analysis, design, development, implementation, and evaluation. Data were collected through teacher needs assessment questionnaires involving eight Sociology teachers, expert validation by three assessment specialists, and field trials with 45 students. Instrument validity was examined using Aiken’s V, while reliability was measured using Fleiss’ Kappa. Practicality was evaluated through questionnaires administered to teachers and students. The results indicate that the developed instrument demonstrates high content validity (Aiken’s V > 0.8), substantial to almost perfect inter-rater reliability, and high practicality, with teacher and student practicality scores of 100% and 80%, respectively. These findings suggest that the instrument is feasible and effective for classroom use. The developed assessment tool provides teachers with a practical means to evaluate students’ 4C skills in social interaction contexts, thereby supporting competency-based assessment practices in Sociology learning.